2013
DOI: 10.1097/mpa.0b013e318258ce4c
|View full text |Cite
|
Sign up to set email alerts
|

Periductal Induction of High Endothelial Venule-Like Vessels in Type 1 Autoimmune Pancreatitis

Abstract: Objectives: Type 1 autoimmune pancreatitis (AIP) is histologically characterized by dense lymphoplasmacytic infiltration and marked storiform fibrosis, manifestations associated with pancreatic ducts. Such periductal lymphocyte recruitment is thought to be elicited by dysregulation of mechanisms governing physiological lymphocyte homing. The present study was undertaken to determine whether vascular addressins including peripheral lymph node addressin (PNAd) and mucosal addressin cell adhesion molecule 1 (MAdC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…26 In that study, we found that MECA-79 antigens were expressed not only on HEV-like vessels but also on exocrine duct-forming epithelium in both pancreases and salivary glands. 26 In that study, we found that MECA-79 antigens were expressed not only on HEV-like vessels but also on exocrine duct-forming epithelium in both pancreases and salivary glands.…”
mentioning
confidence: 82%
“…26 In that study, we found that MECA-79 antigens were expressed not only on HEV-like vessels but also on exocrine duct-forming epithelium in both pancreases and salivary glands. 26 In that study, we found that MECA-79 antigens were expressed not only on HEV-like vessels but also on exocrine duct-forming epithelium in both pancreases and salivary glands.…”
mentioning
confidence: 82%
“…Its initial phase is a morphological and functional change of postcapillary venules into HEV‐like vessels in order to augment lymphocyte migration. As discussed below, endothelial cells in such pathologic conditions express several distinct adhesion molecules involved in lymphocyte recruitment …”
Section: Mechanism Of Lymphocyte Migration Via High Endothelial Venulmentioning
confidence: 99%
“…It is noteworthy that, in chronic abdominal inflammation, expression levels of MAdCAM‐1 on HEV‐like vessels is also upregulated by proinflammatory cytokines such as TNF‐α, interleukin (IL)‐1β and IL‐10 . In addition, these MAdCAM‐1 proteins can be glycosylated with 6‐sulfo sialyl Lewis X‐capped carbohydrates at its mucin‐like domains as abdominal inflammation develops . Thus, lymphocyte tethering and rolling in abdominal inflammation is mediated by two independent molecular interactions: one between MAdCAM‐1 and low‐affinity α 4 β 7 integrin, and the other between 6‐sulfo sialyl Lewis X‐capped glycans and L‐selectin.…”
Section: Mechanism Of Lymphocyte Migration Via High Endothelial Venulmentioning
confidence: 99%
See 2 more Smart Citations